2006
DOI: 10.1161/01.str.0000199081.17935.81
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome as an Independent Risk Factor of Silent Brain Infarction in Healthy People

Abstract: Background and Purpose-Metabolic syndrome (MetS) is associated with an increased risk of the subsequent development of cardiovascular disease or stroke. Moreover, a silent brain infarction (SBI) can predict clinical overt stroke or dementia. We examined the associations between SBI and MetS in apparently healthy individuals. Methods-We evaluated 1588 neurologically healthy subjects (927 males and 661 females) who underwent brain MRI at Seoul National University Hospital Healthcare System Gangnam Center. MetS w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
95
5
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(119 citation statements)
references
References 36 publications
8
95
5
11
Order By: Relevance
“…Previous crosssectional studies showed no differences in brain volume between subjects with and without MetS (5,6), but high HbA 1c has been identified as a risk factor for a greater rate of brain atrophy over 6 years in a prospective study (7). For the relation of MetS with ischemic stroke, contradictory results have been reported (8)(9)(10)(11)(12), as well as for the relation of MetS with WMH (5,13). Not all of these studies used volumetric assessment of WMH and measures of brain atrophy.…”
mentioning
confidence: 99%
“…Previous crosssectional studies showed no differences in brain volume between subjects with and without MetS (5,6), but high HbA 1c has been identified as a risk factor for a greater rate of brain atrophy over 6 years in a prospective study (7). For the relation of MetS with ischemic stroke, contradictory results have been reported (8)(9)(10)(11)(12), as well as for the relation of MetS with WMH (5,13). Not all of these studies used volumetric assessment of WMH and measures of brain atrophy.…”
mentioning
confidence: 99%
“…12 Another study revealed similar prevalence resulting in an age-adjusted SBI prevalence of 5.1% among 994 healthy adults (mean age 49.0 ± 7.7). 13 There were considerable discrepancies in the prevalence rates listed in these studies due to differences in age distribution and the presence of underlying cardiovascular diseases in the study population (Table 1).…”
mentioning
confidence: 81%
“…40 These tendencies were confirmed in middle-aged subjects (adjusted OR [AOR] = 6.52; 95% CI: 4.30-9.90) and in normal healthy adults (mean age 53.6 years, ranged from 20 to 86 years; OR = 2.18; 95% CI: 1.38-3.44). 12,41 Both the full syndrome ($3 of the 5 components) and each of the components were correlated with SBI. It was 12 Though only BP and fasting blood glucose level are usually taken into consideration, TG and AC also need to be considered and should be managed properly to prevent the SBI.…”
Section: Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…SBI has been associated with several cardiovascular risk factors. Previous studies strongly suggest that SBI can be significantly influenced by multiple risk factors, including hypertension, homocysteine levels, cigarette smoking and metabolic syndrome (7)(8)(9)(10)(11). However, relatively little is known about the genes involved in SBI pathogenesis.…”
Section: Silent Brain Infarction (Sbi) Is a Cerebrovascular Disordermentioning
confidence: 99%